An immune-enriched oligo-microarray analysis of gene expression in Manila clam (Venerupis philippinarum) haemocytes after a Perkinsus olseni challenge. Issue 1 (March 2015) - Romero, Alejandro; Forn-Cuní, Gabriel; Moreira, Rebeca; Milan, Massimo; Bargelloni, Luca; Figueras, Antonio; Novoa, Beatriz
Abstract Parasites of the genus Perkinsus cause high mortality and economic losses in bivalves commonly produced in global aquaculture. Although the immune responses of oysters and clams naturally infected with Perkinsus marinus or Perkinsus olseni have been extensively studied, there is not much information on host response at the early stages of infection. In this study, we analysed how P. olseni influences the gene expression profiles of haemocytes from the Manila clam (Venerupis philippinarum) using temporal experimental infections and an immune-enriched microarray. We identified an early phase of infection that was characterised by no mortality and by the increased expression of genes associated with pathogen recognition, production of nitrogen radicals and antimicrobial activity. Cellular processes such as inhibition of serine proteases and proliferation were also involved in this early response. This phase was followed by an intermediate stage, when the pathogen was most likely multiplying and infecting new areas of the body, and animals began to die. In this stage, many genes related to cell movement were over-expressed. Thirty days after infection metabolic pathway genes were the most affected. Apoptosis appears to be important during pathogenesis. Our results provide novel observations of the broader innate immune response triggered by P. olseni at different infection stages.